The octopus tree - Hansen, Chelsea Lorraine, author; Becker, Leslee, advisor; Coke, Pamela, committee member; Alexander, Ruth, committee member (Colorado State University. Libraries, 2018)
"The Octopus Tree" was a story idea I started thinking about when I was teenager. I didn't feel like my writing ability and own mental health was in a positive enough state to write it until I pursued this MFA. "The Octopus Tree" is a result in an interest in assisting adolescents and young adults in dealing with difficult emotions and situations and helping them identify and work through mental illnesses. The story revolves around a set of eighteen-year-old twins: Sawyer has unexpectedly died in a car crash, leaving his brother Jacoby to work through his grief alone. The chapters alternate between the two: Jacoby searches for a lost sketchbook of Sawyer's, while Sawyer exists in Limbo and tries to find ways to stop Jacoby from finding the book.